The impact of audit committee characteristics on aggregate risk disclosure of non-financial firms in China - Wu, Xiao-Yi (2017)
Focusing on the aggregate risk disclosures, this study provides insights on the risk disclosure patterns of a sample of Chinese firms listed in ShenZhen Stock Exchange for the examined the year 2013 and 2015 following the introduction of “Measures for Information Disclosure Assessment of Companies in ShenZhen Stock Exchange”. Using the descriptive statistics, correlation analysis and multiple regression analysis methods, we empirically investigate the association between audit committee characteristics and a number of risk disclosures and the results reveal that: (1) In recent years, the quantity of information disclosure from small and medium enterprise board listed company generally improved, but it still signals a need for further improvements. (2) The firms whose ACs are featured by a high proportion of independent directors and professional experts and high frequency of meeting times will have high incentives to disclose more information in order to inform their investors about the latest risk profile of the company. While firms with small ACs are more likely to withhold risk information. And multiple directorships are found to have no impact on a number of risk disclosures. (3) At last, we discuss the limitation of this dissertation and then provide suggestions for future researches, aiming to extend the literature on risk disclosures. Our results are robust to the use of alternative measures of independent directors in ACs and the findings emphasize the importance of the presence of the number of independent and knowledgeable directors, and meeting times in a year, which have a strong policy implication for Chinese market participants.